2023
DOI: 10.3390/nano13081306
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Apoplastic Extracellular Vesicles Encapsulating Green-Synthesized Silver Nanoparticles to Treat Citrus Canker

Abstract: The citrus canker pathogen Xanthomonas axonopodis has caused severe damage to citrus crops worldwide, resulting in significant economic losses for the citrus industry. To address this, a green synthesis method was used to develop silver nanoparticles with the leaf extract of Phyllanthus niruri (GS-AgNP-LEPN). This method replaces the need for toxic reagents, as the LEPN acts as a reducing and capping agent. To further enhance their effectiveness, the GS-AgNP-LEPN were encapsulated in extracellular vesicles (EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…For instance, nanoparticles extracted and processed from leaves of P. niruri, termed Green-Synthesized Silver Nanoparticles (GS-AgNP-LEPN), when heated after being mixed with AgNO3 solution, have shown efficacy in treating citrus canker caused by Xanthomonas axonopodis. 140 These findings highlight the excellent research value and application potential of PELNs as drug carriers across multiple disciplines. However, the ability of PELNs to load and deliver drugs may be influenced by various factors, primarily encompassing the following aspects: Properties of PELNs: Different PELNs exhibit distinct characteristics, such as variations in size, charge, and stability.…”
Section: Discussion and Outlookmentioning
confidence: 89%
“…For instance, nanoparticles extracted and processed from leaves of P. niruri, termed Green-Synthesized Silver Nanoparticles (GS-AgNP-LEPN), when heated after being mixed with AgNO3 solution, have shown efficacy in treating citrus canker caused by Xanthomonas axonopodis. 140 These findings highlight the excellent research value and application potential of PELNs as drug carriers across multiple disciplines. However, the ability of PELNs to load and deliver drugs may be influenced by various factors, primarily encompassing the following aspects: Properties of PELNs: Different PELNs exhibit distinct characteristics, such as variations in size, charge, and stability.…”
Section: Discussion and Outlookmentioning
confidence: 89%
“…21 Recent studies have demonstrated that EVs loaded with small molecules and proteins exert functional effects. [22][23][24] Similarly, we explored the functional consequences of EVs loaded with S proteins on decidual and chorion cell lines, integral components of the maternal-fetal interface. Our observations reveal distinct gene expression patterns of chemokines, cytokines, and toll-like receptors in maternal decidual and fetal chorion cells in response to maternal exposures.…”
Section: Discussionmentioning
confidence: 99%
“…BEVs may be able to promote the ALP in different NDs, such as PD and AD [16,18,20]. Recent studies have shown that by controlling or promoting the ALP using BEVs, suggesting that BEVs could be a promising therapeutic target for treating NDs focusing on macroautophagy, chaperone-mediated autophagy, and microautophagy [46,53,61]. ALP is very important in removing toxic proteins, like alpha-synuclein in PD, Aβ, and phospho tau in AD, from building up in the brain and trying to clear this toxic proteins when activated.…”
Section: Risk Factors Of Bacterial Extracellular Vesicles In Autophag...mentioning
confidence: 99%
“…BEVs may be able to promote the ALP in different NDs, such as PD and AD [16,18,20]. Recent studies have shown that by controlling or promoting the ALP using BEVs, suggesting that BEVs could be a promising therapeutic target for treating NDs focusing on macroautophagy, chaperone-mediated autophagy, and microautophagy [46,53,61].…”
Section: Risk Factors Of Bacterial Extracellular Vesicles In Autophag...mentioning
confidence: 99%